MARKETING MANAGEMENT IN INCREASING CUSTOMER ATTRACTION AT THE KANGEAN ISLANDS ISLAMIC BOARDING SCHOOL - Na’iesa, Sitti (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Marketing Management is one of the core activities conducted by companies to sustain their existence, grow, and generate profits. Nowadays, educational institutions have also engaged in marketing activities with the aim of emerging as winners in the competition among other educational institutions. In the marketing of educational services, it is essential to consider the needs of users and customers of educational services by offering products that align with the needs of the community. This is achieved through the processing of educational services marketing. Creating attraction among users (customers) in a madrasah indicates that the management of the madrasah can demonstrate its existence by offering and marketing its institution with appealing methods that capture the hearts of the community, making them interested in the institution. Through this research, it is hoped that concrete and sustainable solutions can be found to enhance the appeal of Kangean Islands Islamic Boarding School (Pesantren Kepulauan Kangean). The use of appropriate marketing management strategies will not only have a positive impact on the development of the boarding school itself but will also make a significant contribution to Islamic education in Indonesia. The research object is Pondok Pesantren Zainul Huda Kangean. This study is a case study with data collection techniques involving field observations at Pondok Pesantren Zainul Huda Kangean. From the statements above, it can be concluded that building trust in the community is crucial, supported by promising results and the school's support for all student activities without discrimination. Furthermore, the visible benefits will be advantageous for Pondok Pesantren Zainul Huda Kangean, even though this pesantren is categorized as an old boarding school in the Kangean Islands. Marketing management is one of the fundamental activities conducted by educational institutions to maintain their sustainability, foster growth, and achieve profitability. Therefore, it is clear that marketing is a process that must be undertaken by schools or madrasahs to provide satisfaction to stakeholders and the community